Néologie canadienne de Jacques Viger : Manuscrits de 1810. - Viger, Jacques; Blais, Suzelle; Lapierre, André (Collection Amérique française., 1998)
Jacques Viger - lexicography - nineteenth century - Montreal - Canada.